Comparison of Oral and Dental Health of Children in Need of Special Care According to Disability Status - Yıldız, Semsettin; Tekin, Bahar (My University, 2024)
Purpose: This study aimed to compare oral hygiene, trauma incidence, DMFT, dmft, PUFA, pufa, and the PUFA/pufa index among children with special health care needs based on their disability status. Materials and Methods: This cross-sectional study involved 159 children (mean age 9.5±4 years) from special education institutions in Elazig. Age, gender, disability, presence of dental caries, dental trauma, dental abrasions, oral hygiene and cooperation status of the children were recorded. DMFT/dmft and PUFA/pufa index were used for dental caries scoring. One-way ANOVA and Chi-square tests were used for data analysis with a significance level of 0.05. Results: Statistically significant differences (p<0.05) were found in trauma incidence, oral hygiene, DMFT/dmft, PUFA, pufa, and PUFA/pufa indexes. The highest trauma incidence was in individuals with Down syndrome (p=0.001). Poor oral hygiene was most common in individuals with cerebral palsy (p=0.043). The highest DMFT index was in patients with physical retardation, and the lowest was in patients with Down syndrome (p=0.001). The highest dmft index was seen in patients with physical retardation, while the lowest was in patients with cerebral palsy and mental retardation (p=0.001). The physical retardation group had the highest PUFA and PUFA/pufa index, the learning disability group had the highest pufa index (p=0.001). Conclusion: Children with special needs often struggle with oral and dental health due to physical and mental disabilities. However, we think preventive dentistry practices should be emphasized in these children where cooperation is inadequate. Oral and dental health varies according to disability type.
Keywords: PUFA; disabled children; DMFT; oral hygiene; special health care needs